Grafting of the Organic Functional Groups to the Iron Nanoparticles Surface via Arenediazonium Tosylates; Advanced Materials Research; Vol. 1040 : High Technology: Research and Applications 2014 (HTRA 2014) - Guselnikova O. A. Olga Andreevna (Chemical Technologies, 2014)
Title screen